PENGELOLAAN BANTUAN KEUANGAN BERSIFAT KHUSUS DARI PEMERINTAH KABUPATEN DALAM ANGGARAN PENDAPATAN DAN BELANJA DESA - Johan Satriajaya; Lilik Handajani; I Nyoman Nugraha Ardana Putra (Jurnal Akuntansi Aktual, 2018)
This research aimed to analyse the specially-allocated financial aid policy from district government to village government of Samanta. The fact indicates that there has been a misconduct in budget management, which becomes the main reason to do this research. This research employs a qualitative method, using the phenomenological-hermeneutic approach. Data collection uses an in-depth interview with village financial manager, and supported by observation and documentation. Data analysis applies the method of phenomenological-hermeneutic perspectives. The result shows that specially-allocated financial aid management was not appropriately implemented. This was caused by the inconsistency of local government in implementing its local regulation. District government is using its power discretion and the regulation discretion. High tendency of different interests in implementing the policy has led to a pseudo-statement to empower village government and village society. Thus, it needs better commitment from district government to set aside the interests of certain groups and politics to ensure that the main objective of that policy could be implemented properly.